RESPON TANAMAN PAKCOY (Brassica rapa L.) TERHADAP APLIKASI KOMPOS AMPAS KELAPA DAN NPK MUTIARA (16:16:16) - Zulkifli; Herianto; Putri Lukmanasari (DINAMIKA PERTANIAN, 2022)
The study aimed to determine the response of Pakcoy (Brassica rapa L.) to the Application of Coconut Dregs Compost and Pearl NPK (16:16:16). This study used a factorial completely randomized design consisting of two factors. The first factor is the provision of coconut dregs compost consisting of four levels, namely 0 g/plant, 150 g/plant, 300 g/plant, and 450 g/plant.The second factor is the provision of NPK Mutiara fertilizer (16:16:16) which consists of four levels, namely 0 g/plant, 4 g/plant, 8 g/plant, and 12 g/plant. The parameter observed was the Number of Leaves, Economical Wet Weight, Weight Dry, and Root Volume. The data were statistically analyzed and continued with the Difference Test Real Honest (BNJ) at the 5% level. The results showed that the interaction of coconut dregs compost and pearl NPK 16:16:16 have a significant effect on parameters Number of Leaves, Dry Weight, and Root Volume. Compost best treatment coconut dregs 450 g/plant and NPK pearl 16:16:16 12 g/plant. The main influence effect of coconut pulp compost was significantly on all parameters. The best treatment dose of coconut pulp compost is 450 g/plant. The main influence pearl NPK fertilizer 16:16:16 had a significant effect on all parameters. The best treatment of pearl NPK fertilizer 16:16:16 12 g/plant.